2020
DOI: 10.3390/en13143619
|View full text |Cite
|
Sign up to set email alerts
|

Designing Control Strategies of Aeration System in Biological WWTP

Abstract: The paper presents the complete design processes of novel aeration control systems in the SBR (sequencing batch reactor) wastewater treatment plant (WWTP). Due to large energy expense and a high influence on biological processes, the aeration system plays a key role in WWTP operation. The paper considers the aeration system for a biological WWTP located in the northeast of Poland. This system consists of blowers, the main collector pipeline, three aeration lines with different diameters and lengths, and diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Some studies have shown that COD, BOD, and NH 3 −N are correlated 44 and the energy to power blower fans are actually the main factor in electricity consumption for the removal of COD, BOD, and NH 3 −N. 45 Considering the fact that the smaller the number of highly correlated variables, the more convenient is the practical application of the model, and we assigned the importance of the overlap between variables to the high correlation variable, which led to the low importance of NH 3 −N i /NH 3 −N e . Depending on the request to the accuracy of the model, NH 3 −N i /NH 3 −N e can be neglected during practical usage, but to analyze the model more clearly and completely, we will still take NH 3 −N i /NH 3 −N e into consideration in the following discussion.…”
Section: Regressionsupporting
confidence: 64%
See 1 more Smart Citation
“…Some studies have shown that COD, BOD, and NH 3 −N are correlated 44 and the energy to power blower fans are actually the main factor in electricity consumption for the removal of COD, BOD, and NH 3 −N. 45 Considering the fact that the smaller the number of highly correlated variables, the more convenient is the practical application of the model, and we assigned the importance of the overlap between variables to the high correlation variable, which led to the low importance of NH 3 −N i /NH 3 −N e . Depending on the request to the accuracy of the model, NH 3 −N i /NH 3 −N e can be neglected during practical usage, but to analyze the model more clearly and completely, we will still take NH 3 −N i /NH 3 −N e into consideration in the following discussion.…”
Section: Regressionsupporting
confidence: 64%
“…However, the removal efficiency of NH 3 –N, one of the primary pollutants in sewage, is of relatively low importance to UEC; this is because the primary function of most WWTPs in China is to remove organic matter rather than denitrification, which leads to the lower importance of NH 3 –Ni/NH 3 –N e . Some studies have shown that COD, BOD, and NH 3 –N are correlated and the energy to power blower fans are actually the main factor in electricity consumption for the removal of COD, BOD, and NH 3 –N . Considering the fact that the smaller the number of highly correlated variables, the more convenient is the practical application of the model, and we assigned the importance of the overlap between variables to the high correlation variable, which led to the low importance of NH 3 –N i /NH 3 –N e .…”
Section: Resultsmentioning
confidence: 99%
“…After some discussion of the literature used in Section 2.1, explanations of the hydraulic model [68][69][70][71] (gas flow, pressure, and pipe diameter's mutual dependence) used for the given example of a gas network can be found in Section 2.2 (hydraulics for water networks are explained in [72][73][74][75][76][77] and those for ventilation systems in [78], while an analogy with resistances in electrical networks can be seen in [79,80]). Two iterative methods for the optimisation of pipe diameters are given further in Section 2.3, where the methods are described using an illustrative example.…”
Section: Methodsmentioning
confidence: 99%
“…Relation between gas flow and pressure drop used in this article by Renouard [68,69] (see also [18,70]); • Flow resistance in systems of conduits: gas [71], water [72][73][74][75][76][77] and air [78];…”
mentioning
confidence: 99%
“…This also translates into the efficiency of oxygenation and electricity consumption. In this case, it is necessary to properly model and control the aeration system in the SBR reactor [59,60] In the case of rapid and intensive inflows of wastewater to the wastewater treatment plant, there was a change in the 8 h cycle to the 6 h cycle in SBR reactors, which is a compensation for the buffer capacity of the facility. However, at that time, cases of deterioration in the efficiency of total suspended solids removal from wastewater were observed.…”
Section: Assessment Of the Efficiency Of Sequencing Batch Reactorsmentioning
confidence: 99%